1997
DOI: 10.1017/s0376892997000052
|View full text |Cite
|
Sign up to set email alerts
|

Arrested succession in pastures hinders regeneration of Tropandean forests and shreds mountain landscapes

Abstract: Arrested succession is conspicuous in the abandoned pastures of the Andean piedmont that have encroached upon the tropical montane forests toward higher limits and steeper slopes. Habitat 'shredding' is analysed to depict the current spatial configuration of tropical Andean landscapes, based on fragmentation patterns prompted by seed dispersal ecology and pasture encroachment.Seed dispersal was studied to address the hypo-thesis that seed input constrains the recruitment of montane forest seedlings, thus imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 22 publications
0
72
0
4
Order By: Relevance
“…The present results will help us to understand how seed dispersal occurs during the dry season and allow us to presume that the presence of isolated plants with high crown coverage and densities will promote greater seed rains in pastures. A number of authors have shown that isolated trees have important roles in pastures, such as improving microclimate conditions (Callaway 2007;Derroire et al 2016), increasing soil nutrient levels (Belsky et al 1989;Guevara & Laborde 1993;Sarmiento 1997;Rhoades et al 1998;Otero-Arnaiz et al 1999), facilitating forest recovery (Holl et al 2000;Peña-Domene et al 2014) and serving as stepping stones for species movements between forest fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The present results will help us to understand how seed dispersal occurs during the dry season and allow us to presume that the presence of isolated plants with high crown coverage and densities will promote greater seed rains in pastures. A number of authors have shown that isolated trees have important roles in pastures, such as improving microclimate conditions (Callaway 2007;Derroire et al 2016), increasing soil nutrient levels (Belsky et al 1989;Guevara & Laborde 1993;Sarmiento 1997;Rhoades et al 1998;Otero-Arnaiz et al 1999), facilitating forest recovery (Holl et al 2000;Peña-Domene et al 2014) and serving as stepping stones for species movements between forest fragments.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Primary cloud forest at Maquipucuna Reserve (MR 0°05′ N, 78°37′ W; www.maqui.org ;Sarimento 1997;Myster and Sarmiento 1998;Rhoades et al 1998;Rhoades and Coleman 1999) located 20 km from the town of Nanegalito, Ecuador. This reserve lies between 1200 m and 1800 m a.s.l.…”
Section: Study Sites and Samplingmentioning
confidence: 99%
“…and is classified as tropical lower montane wet/cloud forest (Edmisten 1970). It has deeply dissected drainages with steep slopes and has an annual precipitation of 3198 mm (measured from Nanegal: Sarimento 1997). The temperature ranges yearly between 14 and 25°C, with an average temperature of 18°C…”
Section: Study Sites and Samplingmentioning
confidence: 99%
“…Natural-forest succession following acute degradation at such sites at similar elevations elsewhere in the tropics (Sarmiento, 1997;Slocum et al, 2004) or at lower elevations in Sri Lanka (Cohen et al, 2006;Gunaratne et al, 2010) is sometimes arrested by a dense growth of grasses and/or ferns. At The Totum, however, by 2009 succession by native woody pioneers had been entirely thwarted by the aggressive alien species Austroeupatorium inulifolium (Asteraceae, a Neotropical shrub) and-to a lesser extent-Acacia decurrens (Fabaceae, an Australian tree) (Fig.…”
Section: Introductionmentioning
confidence: 99%